A COMPARATIVE STUDY OF SECONDARY AND HIGHER SECONDARY STUDENTS’ CAREER CHOICES BASED ON PARENTS’ EDUCATION AND INCOME LEVEL (Contemporary Journal of Social Science Review, 2026)
The goal of this study was to investigate the career selection of adolescent students in respect to their parents' education and income status. The quantitative comparative research design was followed and the data was gathered from 357 students who were selected through the use of simple random sampling technique. Structured questionnaire with a Likert scale was used for measuring the career choice. The collected data were analyzed using descriptive statistics and One-Way ANOVA. The results showed students had moderate tendencies towards career choice (M = 3.62, SD = 0.74). The findings also showed that the level of education of parents was significantly different between students' career choices, F(2, 354) = 6.84, p = .001, and income level, F(2, 354) = 4.12, p = .017. In both cases, the career choice tendencies of students from higher education and higher income backgrounds were comparatively more positive. It was found that parents' education and income are important factors influencing students' career selection. Educational institutions are advised to enhance the gendered support and services, including career counseling and career development guidance to students in the lower socio-economic status and ensure that gender parity in access to career development services.